Alfonso I d'Este: music and identity in Ferrara - Shephard, Tim (2010)
Although a great deal of documentation on the patronage of Alfonso I d'Este has already been published, music historians and cultural historians have given little attention to Alfonso's style and importance as a patron of the arts. This study aims to marshal the already-available information to examine Alfonso as a patron of music, placing his interest in music firmly within the context of both his other artistic interests and his role in the turbulent political circumstances of his reign. In so doing it adopts analytical tools developed within the fields of cultural and critical theory and current within literary and art history, although thus far only rarely brought to bear on the history of music in what was once called the High Renaissance. In particular, this study looks at Alfonso's patronage through the thematic of identity, seeking to understand the tasks achieved in the construction of the ruler as a princely persona by both large chapel choirs and private music-making. These concerns will be aligned with the demands placed upon Alfonso by the dynastic, political, military and physical context of his reign. In addressing private music-making at Alfonso's court, this study will seek to make unusually extensive use of the decorations of private courtly spaces - which will be found to offer a frame designed quite self-consciously to give meaning to the musical recreations undertaken therein. The resulting picture will substantially revise our current, somewhat haphazard and uncritical view of Alfonso's music patronage, whilst at the same time proposing new ways to read music's meaning at court. Chapters I and II were presented in abridged form at the Medieval and Renaissance Music Conference 2009 in Utrecht. Parts of Chapters III, IV and VI were presented at the Medieval and Renaissance Music Conference 2008 in Bangor, the Royal Music Association's Research Students' Conference 2009 at King's College, London, and the bodies/music conference, Cork, April 2010. Chapter V, in different versions, was presented at the RMA Annual Conference 2006 in Nottingham and the Association of Art Historians' Annual Conference 2008 in London.